2007
DOI: 10.1177/0020764006074534
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Job Satisfaction in New Zealand Psychiatrists: a National Study

Abstract: This study has demonstrated a high prevalence of burnout and factors associated with it among New Zealand psychiatrists. Further research is needed to ascertain why job satisfaction remains high in the presence of burnout, and factors predisposing to, or protective of, burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
69
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 35 publications
15
69
2
5
Order By: Relevance
“…Burnout was primarily predicted by high frequency of face-to-face interaction with patients, weak work-group cohesion, and perceived unfairness and control; longer career increased the likelihood of burnout. This is in contrast with our findings, as well as with some other studies 20,23 showing a protective effect of years of employment, maybe due to coping strategies or other factors.…”
Section: Commentcontrasting
confidence: 99%
“…Burnout was primarily predicted by high frequency of face-to-face interaction with patients, weak work-group cohesion, and perceived unfairness and control; longer career increased the likelihood of burnout. This is in contrast with our findings, as well as with some other studies 20,23 showing a protective effect of years of employment, maybe due to coping strategies or other factors.…”
Section: Commentcontrasting
confidence: 99%
“…Many other studies carried out by different researchers supported this idea (Lazaro, Shinn, & Robinson, 1984;Shirom, 1989;Jackson, Schwab, & Schuler, 1986;Dolan, 1987;Kumar, et al, 2007;Evans, et al, 2006). Many authors found out that burnout is responsible for low job satisfaction (Lazaro, Shinn & Robinson, 1984;Shirom, 1989;Jackson, Schwab & Schuler, 1986).…”
Section: Discussionmentioning
confidence: 84%
“…The study and found out that a relationship existed between job satisfaction and burnout that is high job satisfaction resulted in low burnout and vice versa. Kumar, et al, (2007) estimated the existence of burnout and the level of job satisfaction among New Zealand psychiatrists. It also ascertained relationships between socio-demographic variables, job satisfaction and burnout by using the Maslach Burnout Inventory (MBI), and a Job Diagnostic Survey (JSS) along with the demographic questionnaire.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A one-year longitudinal study reported that emotional exhaustion is unrelated to job satisfaction (Wright and Cropanzano, 1998). Other researchers showed that job satisfaction remained relatively high despite the high prevalence of burnout and suggested that further research is needed to ascertain why job satisfaction remains high in the presence of burnout (Kumar et al, 2007). Again, collective societies may configure these relationships differently (Walumbwa and Lawler, 2003).…”
Section: Hypothesis 1amentioning
confidence: 99%